Quantitative evaluation of essential medicines lists: the South African case study - Perumal-Pillay, Velisha Ann (BMC Health Serv Res, 2016)
BACKGROUND: The South African (SA) health system has employed an Essential Medicines List (EML) with Standard Treatment Guidelines (STGs) since 1996. To date no studies have reported the changes in SA STG/EMLs. This study describes these changes over time (1996–2013) and compares latest SA STG/EMLs with the latest World Health Organization (WHO) Model EMLs to assess alignment of these lists. METHODS: A quantitative evaluation of SA STGs/EMLs at 2 levels of healthcare was performed to assess changes in the number and ratio of molecules, dosage forms, and additions and deletions of medicines. The most recent WHO EMLs (18th list, 4th list for children) and 2012 priority life-saving medicines for women and children (PMWC) list were compared to the most recent available SA STG/EMLs (Primary Health Care (PHC 2008), Adult Hospital 2012, and Paediatric Hospital 2013) at the time of the research. RESULTS: The number of molecules over the years increased for PHC STG/EMLs but decreased slightly for Adult and Paediatric hospital STG/EMLs. The most additions and deletions over time occurred in the Adult hospital level STG/EML (27 in 2006 and 44 in 2012). A comparison between the most recent SA STG/EMLs and WHO Model EML (18th list) showed that a total of 112 medicines were absent on all SA STG/EMLs. A comparison of medicines for children between the 2013 SA Paediatric Hospital level STG/EML and PMWC indicated that these lists were somewhat aligned for most conditions as only 3 of 14 medicines and 11 of 20 vaccines were absent from SA STG/EMLs. CONCLUSION: This is the first study in SA to investigate changes in National EMLs over time in relation to molecules, dosage forms and therapeutic classes. It is also the first to compare the latest SA STG/EMLs to the WHO Model lists. The results therefore provide insight into the trends and SA STG/EML processes over time.